Elevated plasma ferritin in elderly individuals with high neocortical amyloid-β load. Issue 8 (August 2018) - Goozee, K; Chatterjee, P; James, I; Shen, K; Sohrabi, H; Asih, P; Dave, P; ManYan, C; Taddei, K; Ayton, S; Garg, M; Kwok, J; et al.
Abstract Ferritin, an iron storage and regulation protein, has been associated with Alzheimer's disease (AD); however, it has not been investigated in preclinical AD, detected by neocortical amyloid-β load (NAL), before cognitive impairment. Cross-sectional analyses were carried out for plasma and serum ferritin in participants in the Kerr Anglican Retirement Village Initiative in Aging Health cohort. Subjects were aged 65–90 years and were categorized into high and low NAL groups via positron emission tomography using a standard uptake value ratio cutoff=1.35. Ferritin was significantly elevated in participants with high NAL compared with those with low NAL, adjusted for covariates age, sex, apolipoprotein E ɛ4 carriage and levels of C-reactive protein (an inflammation marker). Ferritin was also observed to correlate positively with NAL. A receiver operating characteristic curve based on a logistic regression of the same covariates, the base model, distinguished high from low NAL (area under the curve (AUC)=0.766), but was outperformed when plasma ferritin was added to the base model (AUC=0.810), such that at 75% sensitivity, the specificity increased from 62 to 71% on adding ferritin to the base model, indicating that ferritin is a statistically significant additional predictor of NAL over and above the base model. However, ferritin's contribution alone is relatively minor compared with the base model. The current findings suggest that impaired iron mobilization is an early event in AD pathogenesis. Observations from the present study highlight ferritin's potential to contribute to a blood biomarker panel for preclinical AD.